دراسة تطبيقات التعليم العميق في مجال الذكاء الاصطناعي , إنجاز جهاز للكشف عن الحيوانات السامة( العقارب والأفاعي) - بورقعه, أيمن; بكري, صلاح الدين; قديري, ياسر (University of El-Oued, 2021)
يمكن للعقارب والأفاعي أن تحقن سمومها في جسم الإنسان ، وقد تقتل الإنسان اذا لم يأخذ الحيطة منهما، لذا فإن الكشف المبكر عنهما أثناء تنقلهما ضروري لحماية الإنسان من مخاطرهما، في هذه المذكرة نقترح نظامًا آليًا جديدًا لاكتشاف العقارب والافاعي والتعرف عليها باستخدام رؤية الكمبيوتر وأساليب التعلم الآلي، تم استخدام تقنيتين تكميليتين لمعالجة الصور في طريقة الكشف المقترحة لضمان كشف دقيق وموثوق عن وجود العقارب والافاعي، الأولى تعتمد على خصائص الهيكل الخارجي للعقارب عند تعرضها للأشعة فوق البنفسجية، والثانية على ملامح شكل العقارب والافاعي. ... " نعتذر لعدم إظهار محتوى هذا الجزء من الملخص نظرا لما یحتويه من معلومات مهمة حول هذا المشروع الذي لم نحصل بعد على الملكية الفكرية الخاصة به "... أظهرت النتائج التي تم الحصول عليها أن النموذج يعمل بكفائه عالية في الكشف عن العقارب، وبسبب توقف جهاز جيتسون نانو الخاص بنا لم نستطع إتمام التجربة الفعلية حول الأفاعي. Scorpions and snakes can inject their toxins into the human body, and they may kill humans if they are not taken care of, so early detection of them while they are on the move is necessary to protect humans from their dangers. In this note, we propose a new automated system to detect and identify scorpions and snakes using computer vision and machine learning methods. Two complementary techniques for image processing were used in the proposed detection method to ensure accurate and reliable detection of the presence of scorpions and snakes, the first depends on the characteristics of the exoskeleton of scorpions when exposed to ultraviolet rays, and the second on the features of the shape of scorpions and snakes. ..." We apologize for not showing the content of this part of Abstract Due to the important information it contains about this project for which we have not yet obtained the intellectual property."... ,The results obtained showed that the model works very well in detecting scorpions, and in view that our kit Jetson Nano has faced a problem during the experiment and stopped, we could not complete the experiment about snakes.
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: العقارب، الأفاعي، التعلم الالي، الشبكات العصبية العميقة.; Scorpions, Snakes, Machine Learning, Deep Neural Networks.